(untitled) (Medicine Today, 2014)
Angular pregnancy is a rare obstetric complication that can be life threatening. In this situation, gestational sac is implanted in the lateral angle of the uterine cavity, medial to the uterotubal junction and round ligament. Angular pregnancy is distinguished from interstitial pregnancy by anatomically, where embryo is implanted lateral to round ligament. The report presented here describes a case of angular pregnancy that was suspected by ultrasound and confirmed during surgery. Laparoscopy can be useful for guiding dilatation & curettage in angular pregnancy and may circumvent the need for invasive surgery or hysterectomy. It has an impact on future fertility. DOI: http://dx.doi.org/10.3329/medtoday.v26i1.21318 Medicine Today 2014 Vol.26(1): 63-65